Undernourished patients do not have increased risk of severe COVID-19 outcomes - Ahmad Fneich; Pierre Poinsot; Christelle Elias; Lioara Restier; Philippe Vanhems; Florent Wallet; Cyrielle Caussy; Antoine Duclos; Noël Peretti (Clinical Nutrition Open Science, 2022)
Background: Undernutrition has been previously identified as a deleterious factor in acute infections. In covid-19 infection, obesity is a risk-factor of severe evolution, but initial undernutrition has not been evaluated yet. Methods: We retrospectively analyzed correlation between nutritional status at admission and severe outcomes (intensive care unit admission, invasive mechanical ventilation requirement and death) of patients hospitalized for confirmed covid-19 infection. Results: Risk of intensive care unit admission and invasive mechanical ventilation requirement was not significantly different between undernutrition and normoweight sub-groups, but increased in excessive weight sub-group (ODDR (IC 95%) 1.048 (1.011-1.086), p = 0.011). Risk of death was the same in all sub-groups. Conclusion: Undernutrition didn't appear as a factor of severe outcomes in covid-19 infection.